Matching as a regression estimator - Dan A. Black (IZA World of Labor, 2015)
“Matching” is a statistical technique used to evaluate the effect of a treatment by comparing the treated and non-treated units in an observational study. Matching provides an alternative to older estimation methods, such as ordinary least squares (OLS), which involves strong assumptions that are usually without much justification from economic theory. While the use of simple OLS models may have been appropriate in the early days of computing during the 1970s and 1980s, the remarkable increase in computing power since then has made other methods, in particular matching, very easy to implement.
Keywords: C10; C14; J00; J08; 330; matching; ordinary least squares (OLS); functional form; regression